Coverage and screening protocols in UNHS programmes in Italy in 2011: A nationwide survey. (September 2013) - Bubbico, Luciano; Tognola, Gabriella; Grandori, Ferdinando
Abstract: Objective: The aim of this study was to provide data on the degree of implementation, coverage and protocols used in Universal Newborn Hearing Screening Programmes (UNHSPs) in Italian birthing hospitals. Methods: Data were collected through a questionnaire that was sent to all birthing hospitals in Italy in 2011. Questionnaires were filled in by the chief of the hospital or by the UNHSPs coordinator. Results: UNHSPs in Italy were activated in 411 (81.3%) birthing hospitals, with 78.3% (413, 212) newborns screened in total. Most (91.8%) of the Italian birthing hospitals used a two-stage (test-retest) TEOAE screening. The personnel performing the screening were nurses in 72.4% of hospitals, paediatricians in 10.2%, technicians in 11.0%, audiologists in 2.2% and external staff in 4.2%. In 80.1% of birthing hospitals, the mean referral rate at first screening performed before discharge was below 5%. Conclusion : The present study revealed that in the last three years screening coverage had a rapid growth from 60.6% in 2008 to 78.3% in 2011, without reaching UNHS coverage greater than 95%, as recommended in international guidelines. Our results suggest that close cooperation between audiological centres and maternity units, together with an efficient protocol for collecting screening data, has a positive impact on the implementation of UNHSPs. It is also crucial to improve the training of screening personnel and provide information and education about newborn hearing screening to paediatricians, neonatologists, gynaecologists, and general practitioners.